Insights into US life expectancy stagnation from birth cohort mortality dynamics - Leah Abrams; Octavio Bramajo; Alyson van Raalte; Mikko Myrskylä; Neil K. Mehta (Proceedings of the National Academy of Sciences, 2026)
US life expectancy remained essentially flat in the 2010s. This trend has occurred in the presence of advancing innovations in medical care, especially for chronic disease, and a growing economy. While research has identified selected contributing factors, including “deaths of despair” and cardiovascular disease mortality stagnation, a comprehensive understanding of the underlying mortality dynamics has not been provided. Notably missing is a systematic evaluation of birth cohort dynamics of mortality, which can reveal whether specific generations are driving adverse trends. Using Lexis diagrams, a powerful tool for visualizing the demographic landscape, we analyzed changes in mortality from 1979–2023 for all-cause mortality and three major cause groups (cardiovascular disease, cancer, external causes). Data included cohorts born between the 1890s and 1980s. Results reveal that both cohort- and period-based processes have produced stalling life expectancy improvement. The 1950–1959 birth cohort represents a transition cohort, wherein there were general improvements in mortality across cohorts born before and general deterioration in mortality across cohorts born after. Alarmingly, cohorts born after 1970 exhibited deteriorating patterns in all major cause groups at young and middle-adult ages. Layered on these cohort dynamics was a broad mortality deterioration that began around 2010 and was experienced by nearly all living adult cohorts at the time, driven primarily by cardiovascular disease mortality. These patterns reflect the complex, multifaceted nature of stalled life expectancy improvements that cannot be attributed to any single cause or temporal mechanism. It also portends an unprecedented longer-run stagnation, or even sustained decline, in US life expectancy.